SMART GARDEN TECHNOLOGY IN THE IMPLEMENTATION OF REAL TIME AUTOMATION IN SMART FARMING-BASED STRAWBERRY CULTIVATION - Gunawan, Sahrul; Nuraini, Sephia (IJISCS (International Journal of Information System and Computer Science), 2025)
This research aims to design and implement a Smart Garden system based on the Internet of Things (IoT) in the cultivation of strawberry plants in real-time. The background of this research is the need for farmers for automation solutions in managing the growing environment of strawberry plants that require certain temperature and humidity conditions. The developed system utilizes the ESP32 microcontroller, soil moisture sensor, and Blynk application as automatic watering monitoring and control media. The method used is a prototyping approach that involves the stages of designing, testing, and evaluating system performance. The test results showed that the system was able to monitor soil conditions and activate the water pump automatically based on the read humidity value. In addition, the Blynk app is capable of displaying data in real-time and providing remote control to users. This system is considered effective in improving watering efficiency, saving water, as well as reducing manual involvement in plant care. Thus, the Smart Garden system built is feasible to be applied to small- to medium-scale horticultural agriculture, especially in areas such as Tanggamus Regency which has high agroclimatic potential but has not been integrated with modern technology.